2007
DOI: 10.2169/internalmedicine.46.0201
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis Accompanied by Systemic Lupus Erythematosus and Autoimmune Hepatitis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
9
0
3
Order By: Relevance
“…The remaining two diseases, SLE and psoriasis, were not uncommon in Taiwan with prevalence of 97.5 and 278.3 per 100 000 population, respectively . There are increasing reports supporting the coexistence of SLE and sarcoidosis with approximately 30 cases reported in the English‐language published work, including four Asian cases . A recent large hospital‐based study in the UK showed significant association between SLE and sarcoidosis (aOR, 8.33; 95% CI, 2.71–19.4) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining two diseases, SLE and psoriasis, were not uncommon in Taiwan with prevalence of 97.5 and 278.3 per 100 000 population, respectively . There are increasing reports supporting the coexistence of SLE and sarcoidosis with approximately 30 cases reported in the English‐language published work, including four Asian cases . A recent large hospital‐based study in the UK showed significant association between SLE and sarcoidosis (aOR, 8.33; 95% CI, 2.71–19.4) .…”
Section: Discussionmentioning
confidence: 99%
“…The association of sarcoidosis with several other autoimmune comorbid diseases as frequently reported before was not demonstrated in our analysis, such as celiac disease, autoimmune hepatitis, inflammatory bowel disease, MS, systemic sclerosis, SLE and psoriasis. 5,9,11,[15][16][17][18][20][21][22][23]35 There were marked racial differences in the prevalence of the first five diseases as mentioned above with the Westerners being more predisposed to those autoimmune comorbidities than the Asian people. [36][37][38][39][40] Hence, the different comorbidity profiles disclosed in our analysis may be attributed to the low prevalence of those diseases in the Taiwanese.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcoidosis is accompanied by many complications, which include various autoimmune diseases that may cause lymphadenopathy [7,8]. Our patients had Sjögren syndrome, rheumatoid arthritis, Hashimoto disease and positive ANAs (×1280).…”
Section: Discussionmentioning
confidence: 97%